2000
DOI: 10.1111/j.1834-7819.2000.tb00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience among publicly‐funded dental patients in Australia, 1995‐96: Type of care and geographic location

Abstract: Health card holders are a financially disadvantaged group and are the target population eligible for publicly-funded dental care. While their health status is generally worse compared with other Australians, there is also considerable variation among card holders. The aims of this study were to describe the oral health status of publicly-funded dental patients by type of care, geographic location and age, and to compare trends over time against other Australian studies. Patients were sampled randomly, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
(11 reference statements)
1
13
0
6
Order By: Relevance
“…Male dentists had an older age distribution than females, with higher percentages in the age groups 40-49 years (31.0 per cent us 25 There was generally close agreement between the distributions of respondents compared to the population of dentisrs", with a tendency for younger dentists to be slightly over-represented, and older dentists to be slightly underrepresented among the respondents. This was adjusted for in the weighting process.…”
Section: Age and Sex Distribution Of Responding Dentistssupporting
confidence: 55%
“…Male dentists had an older age distribution than females, with higher percentages in the age groups 40-49 years (31.0 per cent us 25 There was generally close agreement between the distributions of respondents compared to the population of dentisrs", with a tendency for younger dentists to be slightly over-represented, and older dentists to be slightly underrepresented among the respondents. This was adjusted for in the weighting process.…”
Section: Age and Sex Distribution Of Responding Dentistssupporting
confidence: 55%
“…28,29 The ongoing series of surveys have been useful in gathering baseline information. Uninsured, low income families living in low socio-economic areas in Australia have reported higher rates of edentulism, higher rates of extractions and lower rates of fillings with longer periods since the last visit when compared to people with dental insurance living in more affluent areas.…”
Section: Public Oral Health System In Tasmaniamentioning
confidence: 99%
“…4 The population monitoring and surveillance activity of the Australian Institute of Health and Welfare's Dental Statistics and Research Unit (DSRU) has revealed persistent and significant differences between population groups in adult oral health in Australia for more than a decade, showing that adults who were economically disadvantaged experienced poorer oral health 5 as did Indigenous Australians, 6 older adults in residential care, 7 migrants, 8 rural and remote dwellers, 9 and adults eligible for publicly funded dental care. [10][11][12][13] The linkage by DSRU of 1987/88 National Oral Health Survey data to area indices of socioeconomic status revealed marked inequality in the rates of edentulism and in the prevalence of decayed, missing and filled teeth. 5 Other research found an eightfold difference in the percentage of adults aged 45-64 years who reported edentulism (complete tooth loss) across f ive levels of household income.…”
Section: S Ocial Inequality In Population Oralmentioning
confidence: 99%